Temperament: A Grounded Theory Study On The Formatıon Of Temperament - YALÇIN, Vakkas (Southeast Asia Early Childhood Journal, 2024)
Every baby brings its own temperament with it into the world. Although it is widely accepted by scientists that genetic factors are effective in the formation of temperament, this study aims to examine the possible effects of the pregnancy process on the temperament characteristics of children in line with the experiences of mothers and the role and effects of the father in the pregnancy process and to present a theoretical model explaining this process. The research, which was conducted in the Grounded Theory design, was conducted with a total of 237 mothers consisting of 3 different study groups. The study concluded, important evidence was found that temperament cannot be caused only by biological factors and that the mother's well-being during pregnancy also affects the child's temperament. The study also found that a father supporting the mother during pregnancy (father involvement) was the strongest factor positively influencing the mother's well-being and thus the child's temperament. Based on the research findings, Theoretical Model 1 for temperament formation and Theoretical Model 2 for the father's role in the pregnancy process were presented.